Diskursus Pluralisme Agama dalam Perspektif Aksi Komunikatif - Sri Rosmalina Soedjono (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
Discourse on religious pluralism emerged in the west along with the demands of globalization. Where the owner of power over the modern world wants an order that can bring together the various inhabitants of the world by removing various religious barriers and a single claim to the truth. But this current of view becomes problematic when it collides with the truth by various existing religions. The rejection is very strong, especially from within the Islamic religion. Although the concept of pluralism meets equality in Islam which means diversity, but the fundamental paradigm on which pluralism is built is very different, Western Pluralism departs from the value of secularism while Pluralism in Islam's view is built on the truth value of the revelation of the Qur'an and Hadith. Diversity according to Islam does not require that there is a truth that must be recognized together, but the truth of each religion must be defended. Furthermore, even though humans have different religions and views of life, according to Islam, fellow human beings must be able to work together within the boundaries of worldly affairs to create a just and compassionate life together with fellow human beings, while still holding fast to their respective religions. Although the atmosphere of interfaith dialogue does not need to be prevented and hindered each other, all in an atmosphere of freedom and harmony.